Complexo de inclusão óleo essencial de Lippia Gracilis e ß-Ciclidextrina : uma alternativa no controle das larvas de Aedes Aegypti - Cerpe, Patricia (2013)
In terms of morbidity and mortality, dengue is considered the important human viral disease transmitted by mosquitoes, caused by virus of the family Flaviridae, one of the main problems in public health in the world, due to the great potential for the development of several forma and lethal disease. Another problem about dengue control is the population of Aedes aegypti resistant to toxicity of chemical insecticides, such as temephos. This work involved the formulation and characterization of inclusion complex of essential of Lippia gracilis (LGEO), with potent larvicidal effect against Aedes Aegypti Linnaeus larvae in β-cyclodextrin (β-CD), aiming to improve oil solubility in aqueous serving as a strategy for obtaining new products larvicides. Inclusion complexes were obtained by kneading and coevaporation. The complexes obtained by paste and co-evaporation was assessed the influence of the co-solvent used to preparation the complexes by paste with water (PMW), kneading with ethanol / water (PME) co-evaporation with water (COW) and co-evaporation of ethanol / water (COE) methods. The chemical LGEO constituents were identified by gas chromatography coupled to mass spectrometer (GC / MS) where the complex (PMW) was superior in the inclusion of carvacrol with a content of 15.25% compared with the another techniques preparation. The complexes were characterized by thermogravimetry (TG / DTG), the moisture content by Karl-Fischer, differential scanning calorimetry (DSC), X-ray diffraction (X-RD), spectroscopy in the infrared with Fourier transform ( FTIR) and ultra violet (UV-vis), scanning electron microscopy (SEM) and solubility tests. According to the results obtained by GC / MS the major constituent of OELG was carvacrol (46.7%). In TG / DTG and DSC revealed the complex displacement in the range of thermal degradation of the oil to higher temperature ranges indicating a gain of thermal stability. In the analyzes of (X-RD) of the complexes showed the loss of crystalline order compared to pure β-CD. The scanning electron microscopy (SEM) showed changes in particle shapes and morphology of the complex when compared with pure β-CD. The larvicidal assay against Aedes aegypti larvae were carried out with the Rockefeller strain in the third stage (L3), and mortality was observed after 24 hs. The phase solubility diagram at different temperatures, the values of the stability complex of the constant (PMW), was demonstrates be stable and water soluble the interaction complex OELG / β-CD. Aedes aegypti larvae were susceptible to the composition of OELG, carvacrol and complex (PMW) using the method of Probit analysis. The larvicidal activity of the complex (PMW) LC50 was 33 ppm, close to that of pure oil LC50 39 ppm and may be a suitable alternative to biolarvicida dengue control programs.